Evaluasi Kinerja Sumber Daya Manusia di Badan Penanggulangan Bencana Daerah Provinsi Nusa Tenggara Barat - Selamat Jalaludin (Society, 2024)
Drought is a recurring disaster in West Nusa Tenggara Province, and effective disaster management relies heavily on the performance of human resources. This study aims to evaluate the performance of the human resources at the Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah, BPBD) in addressing drought disasters in the province. The research employed a descriptive method with a qualitative approach, collecting data through direct observation and documentation. Data analysis followed the document analysis model developed by Miles and Huberman, which involves data reduction, data presentation, and conclusion. The findings indicate that the human resources of BPBD West Nusa Tenggara Province (BPBD-NTB) have been effective in preventing and recording the impacts of drought in the region. Furthermore, BPBD-NTB has implemented comprehensive emergency planning, infrastructure development projects such as dam construction, and public awareness initiatives, including socialization and education programs to enhance community knowledge about drought risks and preventive actions. Reporting mechanisms were also identified as an essential component of employee performance, particularly for addressing ongoing and future drought challenges. Over the past five years, the study found that Central Lombok Regency experienced the most significant impact, with 1,368,652 people affected by drought. This underscores the critical role of human resources in disaster management and mitigation efforts in West Nusa Tenggara Province.